2011
DOI: 10.1002/chp.20101
|View full text |Cite
|
Sign up to set email alerts
|

The Integrated Joslin Performance Improvement/CME Program: A New Paradigm for Better Diabetes Care

Abstract: Ongoing continuing medical education is an essential component of life-long learning and can have a positive influence on patient outcomes. However, some evidence suggests that continuing medical education has not fulfilled its potential as a performance improvement (PI) tool, in part due to a paradigm of CME that has focused on the quantity of continuing medical education credits attained rather than the quality of outcomes. The Joslin Diabetes Center has undertaken a new performance-based CME program model t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…More precisely, acknowledging that medical personnel is employed in a most pertinent working field, the impetus for flexibility, adaptability and improved performance has come to the fore. Throughout the contemporary literature [ 4 - 6 ], the necessity for bringing physicians up-to-date with an evolving body of knowledge, so as to improve performance and optimize outcomes, is emphasized, while delivering CME interventions has become a major enterprise, globally [ 4 , 7 ] .…”
Section: Introductionmentioning
confidence: 99%
“…More precisely, acknowledging that medical personnel is employed in a most pertinent working field, the impetus for flexibility, adaptability and improved performance has come to the fore. Throughout the contemporary literature [ 4 - 6 ], the necessity for bringing physicians up-to-date with an evolving body of knowledge, so as to improve performance and optimize outcomes, is emphasized, while delivering CME interventions has become a major enterprise, globally [ 4 , 7 ] .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Based on this rationale, the performance measures selected by the faculty for this PI CME activity addressed the topics of actively assessing and accurately diagnosing MS-related symptoms; selecting appropriate treatments; and monitoring the efficacy of non-pharmacologic and pharmacologic therapies. Our outcomes demonstrated that PI CME is a viable approach for quality improvement in MS as it resulted in significant increases in the frequency of assessment and care plan documentation for several important MS symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] In this QI activity, data from SNFs participating in the baseline assessment (stage A) were aggregated and compared against data from SNFs participating in reassessment phase (stage C; Table 1). …”
Section: Methodsmentioning
confidence: 99%